Pemodelan VAR untuk Menganalisis Dampak Perubahan Nilai Tukar USD terhadap Volume Ekspor Migas Indonesia (2019-2023) - Rowa, Augusta; Elisabeth, Yolanda Febiola; Ringka, Kristina; Kurniadi, Kurniadi; Chawala, Juhi; Beautrik, Mei Laura; Isa, Isa; Silaban, Desi Natalia; Ompusunggu, Dicky Perwira (Innovative: Journal Of Social Science Research, 2025)
Many This study uses a Vector Autoregression (VAR) model to examine the impact of changes in the USD exchange rate on Indonesia's oil and gas export volume in the 2019-2023 period. Time series data analysis shows that the USD exchange rate and oil and gas export volume data become stationary after the first differentiation transformation, with an optimal lag of two periods. The resulting VAR model is also proven to be stable. The results of the Granger causality test show that there is no significant causal relationship between the USD exchange rate and oil and gas export volume at the 5% significance level. This finding suggests that other factors, not included in this model, may play a role in the dynamics of the relationship between the exchange rate and oil and gas exports. This study provides an understanding of the dynamics of the relationship between the USD exchange rate and oil and gas export volume in Indonesia, and emphasizes the need for a more comprehensive analysis that considers other factors that may contribute to the relationship.